Escaping from the poverty trap with social innovation: A social microcredit programme in Hungary - György Molnár; Attila Havas (Hungarian Academy of Sciences, Institute of Economics, 2019)
This paper describes a Hungarian social microcredit programme, called Kiútprogram and discusses the major lessons drawn from its operation. It was launched some 10 years ago as an adaptation of the Grameen model to the Hungarian circumstances to decrease the level of prejudice and discrimination against the Roma and improve their living conditions in the most remote, deprived areas of Hungary; microlending has been understood and introduced as a device to achieve these aims -and not as a profit-seeking business activity.During the almost ten-year long learning process, from the simple adaptation of the Grameen model the Kiútprogram has arrived to the denial of the most important features of joint liability in group lending, namely the application of the devices of social collateral. Experience has also shown that a loan itself is not sufficient to assist escaping fromthe poverty trap. Without knowledge transfer and without inter-community connection building - at least in the case of discriminated minorities - the effect of the loan may even be detrimental. In a modern society not only physical, but also social and cultural capital is needed to run a successful business in the formal sector of the economy.In the Kiútprogram's model the loan plays a crucial role in escaping from the aspiration trap, and thus helps overcome learned helplessness. Loans without any - financial or social - collateral signal that the lender trusts the client, not only in her honesty, but also in her abilities. This method of lending strongly suggests to the clients the conviction that she is able of achieving a business success. Neither financial aid, nor loan with (social) collateral is suitable to reach this effect.
Keywords: G21; L31; O35; J24; J71; 330; microcredit; group lending; empowerment; poverty trap; aspiration trap; Roma minority